2003
DOI: 10.1074/jbc.m308439200
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the Nrf1 and Nrf2 Transcription Factors Results in Early Embryonic Lethality and Severe Oxidative Stress

Abstract: Nrf1 and Nrf2 are members of the CNC family of bZIP transcription factors that exhibit structural similarities, and they are co-expressed in a wide range of tissues during development. Nrf2 has been shown to be dispensable for growth and development in mice. Nrf2-deficient mice, however, are impaired in oxidative stress defense. We previously showed that loss of Nrf1 function in mice results late gestational embryonic lethality. To determine whether Nrf1 and Nrf2 have overlapping functions during early develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
243
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(261 citation statements)
references
References 51 publications
(57 reference statements)
9
243
0
Order By: Relevance
“…Recently, it has been shown that Nrf2 and its downstream effectors act as critically important regulators in the protection of cells from oxidative stress and chemical-induced damage of liver and lung tissues by the regulation of intracellular redox status (Chan and Kan 1999;Chan et al 2001). It was demonstrated that Nrf2 knockout mice are more sensitive to hyperoxic injury of lung tissue (Cho et al 2002) and Nrf2 deficiency results in early embryonic lethality with severe oxidative stress (Leung et al 2003). In addition to its role in regulating ROS levels, several recent studies have showed that the Nrf2 pathway regulates immune and inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that Nrf2 and its downstream effectors act as critically important regulators in the protection of cells from oxidative stress and chemical-induced damage of liver and lung tissues by the regulation of intracellular redox status (Chan and Kan 1999;Chan et al 2001). It was demonstrated that Nrf2 knockout mice are more sensitive to hyperoxic injury of lung tissue (Cho et al 2002) and Nrf2 deficiency results in early embryonic lethality with severe oxidative stress (Leung et al 2003). In addition to its role in regulating ROS levels, several recent studies have showed that the Nrf2 pathway regulates immune and inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest the possibility of cross talk between Nrf2 and NF-κB signaling event. It has been known that MAPKs regulate many cellular events, including differentiation, proliferation, and apoptosis (Lewis et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Its role in oxidant defense has been well demonstrated in Nrf2-deficient mice. These mice express decreased levels of various phase II enzymes and antioxidant genes and are extremely susceptible to oxidant-induced injuries [58][59][60][61][62]. It is now clear that the Nrf2 activity is precisely regulated.…”
Section: Discussionmentioning
confidence: 99%
“…The primary astrocyte of Nrf2 À/À mice is also more susceptible to oxidative stress and inflammation than that of Nrf2 þ / þ mice. 6 Leung et al 7 showed that deficiency of Nrf2 results in early embryonic lethality with severe oxidative stress. These observations, collectively, imply that Nrf2 is a master regulator of ARE-driven transcriptional activation for antioxidant genes in maintaining the homeostasis of Redox status within cells.…”
Section: Introductionmentioning
confidence: 99%